Pengaruh Pajak Penghasilan dan Corporate Governance Pada Manajemen Laba Perusahaan Pertambangan - Halimi, Kresna Koharwaranto; Dwija Putri, IGAM Asri (E-Jurnal Akuntansi; Vol 21 No 3 (2017)DO - 10.24843/EJA.2017.v21.i03.p03, 2017)
The purpose of this study was to test how the income tax and the corporate governance on earnings management. Modifikasian Jones model is used to calculate discretionary accruals. As for corporate governance using a proxy board size and audit committee. Data analysis technique used is the test of normality, heteroscedasticity, multicollinearity, autocorrelation and multiple linear regression analysis. The results showed that the income tax has no effect on earnings management, meaning a lack of correlation between income tax and profit management. Board size no negative effect on earnings management, where such conditions can be due to the difficulty of coordination between the members of the council and it inhibits the supervisory process should be the responsibility of the board of commissioners. The audit committee has a negative effect on earnings management, which means that if the audit committee increased, it will result in a decrease in earnings management practices
Keywords: earnings management, discretionary accruals, income tax, corporate governance